Developing a Training Program to Diversify the Biomedical Research Workforce. (August 2019) - Rubio, Doris M.; Hamm, Megan E.; Mayowski, Colleen A.; Nouraie, Seyed Mehdi; Quarshie, Alexander; Seto, Todd; Shaheen, Magda; Soto de Laurido, Lourdes E.; Norman, Marie K.
Abstract : The National Institutes of Health has made considerable investments to diversify the biomedical research workforce. Towards this goal, the authors partnered with representatives from several minority-serving institutions (MSIs) to develop training for the next generation of researchers. To ensure the most effective training program, the authors conducted a needs assessment with junior and senior investigators from the partnering MSIs. In 2016, the authors conducted focus groups and interviews with 23 junior investigators as well as in-depth interviews with 6 senior investigators from the partnering institutions with the goal of identifying specific areas of training and support that would help junior investigators at MSIs develop and sustain research careers. The data were transcribed and coded, and thematic analysis was conducted. The authors determined four areas in which training and support were needed: training in the "informal curriculum" (skills not covered in traditional clinical research courses), protected time for research training, opportunities to create career-advancing work products, and networking opportunities. The themes that were identified informed the development of the LEADS (Leading Emerging and Diverse Scientists to Success) program. The program consists of 10 instructor-led online modules each lasting approximately one month in duration with weekly synchronous sessions. Scholars are expected to be able to devote at least 20% of their time to the program. Abstract : Supplemental Digital Content is available in the text.